Ureteral stent placement and immediate graft function are associated with increased risk of BK viremia in the first year after kidney transplantation. (28th December 2016) - Maliakkal, Joseph G.; Brennan, Daniel C.; Goss, Charles; Horwedel, Timothy A.; Chen, Howard; Fong, Dennis K.; Agarwal, Nikhil; Zheng, Jie; Schechtman, Kenneth B.; Dharnidharka, Vikas R.
Summary: Ureteral stent (UrSt) placement has been shown to be a significant independent risk factor for BK viruria, viremia, and BK virus nephropathy. We assessed whether this observation could be validated at our high volume kidney transplant center that has had a strong historical focus on BK virus nephropathy detection. We performed a retrospective case–control study of adults receiving a kidney‐only transplant and followed for 1 year between 2004 and 2011 with uniform immunosuppression and use of blood BK virus PCR screening protocol. Among 1147 patients, 443 (38.6%) received a UrSt and 17.2% with a UrSt had BK viremia versus 13.5% without stent (odds ratio 1.33; 95% CI: 1.00–1.78). We confirmed a previously reported association between immediate graft function (IGF) and higher rate of BK viremia (15.7% vs. 5.9% in patients without IGF). On multivariable competing risks Cox regression in patients with IGF, UrSt (adjusted hazard ratio [aHR] 1.35; 95% CI: 1.04–1.75) and African American race (aHR 1.47; 95% CI: 1.04–2.09) significantly increased the risk for BK viremia. In the largest sample size to date, we confirmed that UrSt placement during kidney transplant surgery is a risk factor for BK viremia within the first year post‐transplant and that IGF is associated with BK viremia.